2021
DOI: 10.3389/fsufs.2021.715270
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic PGPB Improves Plant Growth and Quality, and Modulates the Bacterial Community of an Intercropping System

Abstract: The intercropping of ryegrass and red clover constitutes a sustainable alternative to mitigate the adverse effects of intensive livestock production on grassland degradation by increasing forage yield and quality. The implementation of biofertilization technologies has been widely used to improve soil nutritional properties, and therefore has the potential to ensure the success of this multicrop system. To determine the impact of bioaugmentation on forage growth and quality, as well as the associate changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…This was a relevant condition of this study provided by the soil used, low P availability (12.28 mg kg −1 ), and reduced doses of P fertilizer applied. Abiotic stresses in plants (e.g., nutritional, saline, or drought stress) have been reported in research developments to strongly influence the potential of these microbes to promote growth (Moreno-Galván et al, 2020;Cortés-Patiño et al, 2021;Mendoza-Labrador et al, 2021;Pardo-Diaz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This was a relevant condition of this study provided by the soil used, low P availability (12.28 mg kg −1 ), and reduced doses of P fertilizer applied. Abiotic stresses in plants (e.g., nutritional, saline, or drought stress) have been reported in research developments to strongly influence the potential of these microbes to promote growth (Moreno-Galván et al, 2020;Cortés-Patiño et al, 2021;Mendoza-Labrador et al, 2021;Pardo-Diaz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The Pearson analysis showed a moderate (r = 0.4) correlation between total carotenoids and non-photochemical quenching ( Figure 4 ). The higher content of pigments in plants inoculated with the bacterial strains could be associated with their ability to fix nitrogen, as these bacteria have been shown to grow in nitrogen-free medium [ 24 ] and to improve the nitrogen content in perennial ryegrass [ 28 ]. The potential of Herbaspirillum to increase the nitrogen content has also been previously reported in crops like maize [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…AP21 and D7 were isolated from Kikuyu grass, while T88, a symbiotic nitrogen-fixing bacterium, was isolated from nodules of red clover ( Trifolium pratense ). We selected these strains because previous research has demonstrated their ability to promote red clover and ryegrass growth under abiotic stress (drought) conditions [ 24 , 25 ] and to optimize P and N use [ 20 , 26 ]. The guaranteed concentration of each strain was 1 × 10 CFU for strains AP21, T88, and D7.…”
Section: Methodsmentioning
confidence: 99%
“…These strains were selected because previous studies have demonstrated their ability to promote growth in associated ryegrass and red clover pastures under abiotic stress conditions due to drought [ 24 , 25 ]; in addition, Santos-Torres et al [ 20 ] reported AP21’s capacity to solubilize Pi and T88’s ability to mineralize organic P (Po). Likewise, Pardo-Díaz et al [ 26 ] found that AP21 and D7 showed potential in reducing nitrogen (N) fertilization. In this context, the use of organic and inorganic P sources in combination with PSB has the potential to contribute to increasing soil P availability and improving pasture productivity.…”
Section: Introductionmentioning
confidence: 99%